Improving transient expression in N. benthamiana by suppression of the Nb-SABP2 and Nb-COI1 plant defence response related genes - Kopertekh, Lilya (Frontiers in Plant Science, 2024)
Currently transient expression is one of the preferred plant-based technologies for recombinant protein manufacturing, particularly in respect to pharmaceutically relevant products. Modern hybrid transient expression systems combine the features of Agrobacterium tumefaciens and viral vectors. However, host plant reaction to Agrobacterium-mediated delivery of gene of interest can negatively affect foreign protein accumulation. In this study, we investigated whether the modulation of plant immune response through knockdown of the Nb-SABP2 and Nb-COI1 N. benthamiana genes could improve recombinant protein yield. In plants, the SABP2 and COI1 proteins are involved in the salicylic acid and jasmonic acid metabolism, respectively.We exemplified the utility of this approach with the green fluorescence (GFP) and β nerve growth factor (βNGF) proteins: compared to the tobacco mosaic virus (TMV)-based vector the Nb-SABP2 and Nb-COI1-suppressed plants provided an increased recombinant protein accumulation. We also show that this strategy is extendable to the expression systems utilizing potato virus X (PVX) as the vector backbone: the enhanced amounts of βNGF were detected in the Nb-SABP2 and Nb-COI-depleted leaves co-infiltrated with the PVX-βNGF. These findings suggest that modulating host plant reaction to agrodelivery of expression vectors could be useful for improving transient foreign protein production in N. benthamiana.